Skeletal muscle as a regulator of the longevity protein, Klotho - Avin, Keith G.; Coen, Paul M.; Huang, Wan; Stolz, Donna B.; Sowa, Gwendolyn A.; Dubé, John J.; Goodpaster, Bret H.; O'Doherty, Robert M.; Ambrosio, Fabrisia (Frontiers in Physiology, 2014)
Klotho is a powerful longevity protein that has been linked to the prevention of muscle atrophy, osteopenia, and cardiovascular disease. Similar anti-aging effects have also been ascribed to exercise and physical activity. While an association between muscle function and klotho expression has been previously suggested from longitudinal cohort studies, a direct relationship between circulating klotho and skeletal muscle has not been investigated. In this paper, we present a review of the literature and preliminary evidence that, together, suggests klotho expression may be modulated by skeletal muscle activity. Our pilot clinical findings performed in young and aged individuals suggest that circulating klotho levels are upregulated in response to an acute exercise bout, but that the response may be dependent on fitness level. A similar upregulation of circulating klotho is also observed in response to an acute exercise in young and old mice, suggesting this may be a good model for mechanistically probing the role of physical activity on klotho expression. Finally, we highlight overlapping signaling pathways that are modulated by both klotho and skeletal muscle and propose potential mechanisms for cross-talk between the two. It is hoped that this review will stimulate further consideration of the relationship between skeletal muscle activity and klotho expression, potentially leading to important insights into the well-documented systemic anti-aging effects of exercise.